Shape anisotropic iron oxide-based magnetic nanoparticles: synthesis and biomedical applications - Andrade, Raquel G. D. (2020)
Research on iron oxide-based magnetic nanoparticles and their clinical use has been, so far, mainly focused on the spherical shape. However, efforts have been made to develop synthetic routes that produce different anisotropic shapes not only in magnetite nanoparticles, but also in other ferrites, as their magnetic behavior and biological activity can be improved by controlling the shape. Ferrite nanoparticles show several properties that arise from finite-size and surface effects, like high magnetization and superparamagnetism, which make them interesting for use in nanomedicine. Herein, we show recent developments on the synthesis of anisotropic ferrite nanoparticles and the importance of shape-dependent properties for biomedical applications, such as magnetic drug delivery, magnetic hyperthermia and magnetic resonance imaging. A brief discussion on toxicity of iron oxide nanoparticles is also included.